Kajian Teologi Pastoral terhadap Artificial Intelligence dalam Praktek-praktek Religius - Raka, Andreas Gandhi (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
Lately, artificial intelligence has been rapidly advancing and is increasingly being utilized, both by experts in various fields and by the public in common. This article provides a study of the theology of pastoral on the specific use and influence of AI in ChatGPT. By reviewing the utilization of chatbot in various religious practices such as sermon creation, spiritual guidance, and access to religious teachings, this research explores the extent to which chatbot can assist in religious practices. This research includes evaluation of its usage and consideration of its risks associated with the use of AI technology particularly in religious practices. Exploring AI chatbots' potential could help technology as catalysts for transformation of religious practices nowaday. Furthermore, we can direct technology as a tool to enrich faith and the spiritual dimensions of humanity in this digital era.AbstrakBelakangan ini artificial intelligence berkembang dengan pesat dan semakin banyak digunakan, baik dalam bidang ahli maupun oleh masyarakat pada umumnya. Artikel ini memberikan kajian teologi pastoral terhadap penggunaan dan pengaruh AI secara khusus dalam chatbot ChatGPT. Dengan melihat penggunaan chatbot dalam beberapa praktik religius, seperti pembuatan khotbah, bimbingan rohani, dan akses terhadap ajaran iman, penelitian ini mengeksplorasi sejauh mana chatbot dapat membantu dalam praktek religius. Penelitian ini juga meliputi evaluasi dan pertimbangan mengenai resiko penggunaan teknologi AI untuk melihat dampak yang mungkin muncul. Dengan mengeksplorasi chatbot AI, diharapkan teknologi dapat menjadi katalisator transformasi praktik religius. Selain itu, kita dapat menjaga agar teknologi tetap dapat menyentuh dan memperkaya iman dan atau dimensi spiritualitas manusia di era digital ini.